2017
DOI: 10.3892/ijmm.2017.3105
|View full text |Cite
|
Sign up to set email alerts
|

Integrating microRNA and messenger RNA expression profiles in a rat model of deep vein thrombosis

Abstract: Deep vein thrombosis (DVT) is a disease involving multiple genes and systems. MicroRNAs (miRNAs) represent a class of non-coding small RNAs that post-transcriptionally suppress their target genes. The expression patterns of miRNA and messenger RNA (mRNA) in DVT remain poorly characterized. The aim of the present study was to evaluate miRNA and mRNA expression profiles in a stasis-induced DVT rat model. Male SD rats were randomly divided into three groups as follows: DVT, sham and control. The inferior vena cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…Clinical manifestations of DVT are primarily lower limb swelling, ulceration, and necrosis, which may seriously limit patients' quality of life . Existing literature has highlighted the participation of miRNAs in almost all pathological and physiological processes including DVT . In this study, we established in vivo LEDVT mouse models and identified that miR‐103a‐3p might be an endogenous regulator of LEDVT.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Clinical manifestations of DVT are primarily lower limb swelling, ulceration, and necrosis, which may seriously limit patients' quality of life . Existing literature has highlighted the participation of miRNAs in almost all pathological and physiological processes including DVT . In this study, we established in vivo LEDVT mouse models and identified that miR‐103a‐3p might be an endogenous regulator of LEDVT.…”
Section: Discussionmentioning
confidence: 95%
“…21 Existing literature has highlighted the participation of miRNAs in almost all pathological and physiological processes including DVT. 22 In this study, we established in vivo LEDVT mouse models and identified that miR-103a-3p might be an endogenous regulator of LEDVT. Restoration of miR-103a-3p could potentially prevent LEDVT development via inhibiting CXCL12 expression.…”
Section: Mir-103a-3p Regulates Macrophage Polarization and Venous Tmentioning
confidence: 99%
“…The rats were randomly divided into three groups (n = 10 per group): a control group, a DVT group, and a sham group. According to our previous study 33 , the rats in the DVT group were anesthetized with 10% chloral hydrate. After exploring the IVC, all side branches were ligated.…”
Section: Methodsmentioning
confidence: 99%
“…The level of the miRNA-17-92 cluster increases 24 h after coronary occlusion [14]. In addition, miR-92a-3p is upregulated in the vascular tissues in a rat model of deep vein thrombosis [15]. miR-92a-3p is very sensitive to changes in shear stress.…”
Section: Introductionmentioning
confidence: 99%